Faktor-faktor yang Memengaruhi Keberhasilan Seorang Pemimpin dalam Ranah Pendidikan Islam - Alghozi, Alan Alifudin; Masduki, Yusron; Safrial, Ridho (Al Hikmah: Jurnal Studi Keislaman, 2023)
A leader who achieves success must have several factors that are the key to success. In this research article, discusses anything that can be a factor in one's success in becoming a leader, especially in relation to Islamic education. This research uses the Library Research model by taking research data that has been presented from other sources such as journals, books, and so on. The research findings show that there are several factors that have an impact on the success of a leader in the realm of Islamic education. From the results of the research in this article, it can be concluded that the sustainability of an educational institution develops and succeeds depending on how the captain (leader) is. A leader who has good morals and adheres to all religious and cultural norms must be worthy of the title of successful leader. Himself as an example and command as well as driving force in the territory of his leadership. Keywords: Factors, Leader Success, Islamic Education.